Uses and Practices of Computer Application in Demographic Research Regarding Nepal - Adhikari, Govinda Prasad (Patan Pragya, 2021)
The computer was used to model, simulate and analyze social phenomena in the research. This study aims to analyze the uses of computer software in demographic research in Nepal. Information was gathered from secondary sources from reports of GOs and NGOs, manuals and guidelines of various software packages. Information was taken from the United Nations software package, World Health Organization, United Nations Population Funds and software package of the U.S. Census Bureau. Other’s information was taken from the National Housing and Census and Demographic Health Survey of Nepal. To achieve the objective of this study data are analysed in a descriptive method. This study has focused on computer software mainly SPSS, Mort Park, CS Pro, and STATA. The roles of computer have been helpful in quantitative research. Its role is also important when the research is on a large sample. The computer assists the researcher throughout different phases in the quantitative research process. The major five phases of the research process are the conceptual phase, design and planning phase, empirical phase, analytic phase, and dissemination phase. The use of computer software is helpful in data entry, data editing, and data management. The data analysis software is supportive of processing and manipulating information and analyzing the relationship between variables. Therefore, the use of computer software can save money, time, and resources in research. In the case of Nepal, the Integrated Microcomputer Processing System (IMPS) was in the census in 1991. STATA and SPSS software packages were used for data editing, management, and tabulation of the census results. Open Data Kit platform and CAPI was used for data collection and the CS Pro software was used for data management in various demographic studies in Nepal.